Sierra Leone Economic Update, June 2019 : Financial Inclusion for Economic Growth and Development - World Bank Group (World Bank, Washington, DC, 2019)
Sierra Leone’s macroeconomic performance continued to improve but at a slower pace. Yet there are significant downside risks to the medium-term economic outlook.